متطلبات التحول لتطبيق ميزانية البرامج و الأداء دراست حالة – جامعة محمد الشريف مساعدية – سىوق أهراس - وردة سقني; خولة دريفول (My University, 2022)
The study aimed to identify the method of preparing program and performance budgets in Algeria in general, and in the Algerian Ministry of Higher Education in particular. Descriptive and analytical to conduct the study. Accordingly, the study concluded that both the item budget and the program and performance budget contribute to achieving performance oversight at the university, and the process of applying program and performance budgets faces multiple difficulties to a high degree. In addition, there are necessary requirements for the success of the process in the higher education sector, as the study showed that the link was not achieved. The appropriateness between the strategic objectives of the Ministry of Higher Education and the approved objectives for measuring performance in the draft general budget.